Chirality: Three Dimensional Chiral Metamaterial Nanospirals in the Visible Range by Vertically Compensated Focused Ion Beam Induced‐Deposition (Advanced Optical Materials 2/2014). Issue 2 (February 2014) - Esposito, Marco; Tasco, Vittorianna; Todisco, Francesco; Benedetti, Alessio; Sanvitto, Daniele; Passaseo, Adriana
<x xml:space="preserve">Abstract</x> Chiral metamaterials in the form of metallic nanospirals allow the exploration of chiro‐optical phenomena, such as dichroic selection. On page 154, by exploiting a highresolution nanofabrication technique based on focused ion beam‐induced deposition, M. Esposito et al. accurately control the 3D evolution of the nanostructures, with the fabricated nano‐objects showing a high circular dichroism in the visible range, paving the way towards advanced chiral photonic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>